How to Read and Interpret FTIR Spectroscope of Organic Material - Nandiyanto, Asep Bayu Dani; Oktiani, Rosi; Ragadhita, Risti (Indonesian Journal of Science and Technology, 2019)
Fourier Transform Infrared (FTIR) has been developed as a tool for the simultaneous and quantitative determination of organic components, including chemical bond, as well as organic content (e.g. protein, carbohydrate and lipid). However, until now, there is no further information for the detailed information in the FTIR peaks. The objective of this study was to demonstrate how to read and assess chemical bond and structure in the organic material. The analysis was then compared with the literatures. The step-by-step method on how to read the FTIR data was presented, including reviewing simple to the complex organic materials. This study is potential to be used as a standard information on how to read FTIR peaks in the biochemical and organic materials.